Hate Speech in Times of the COVID-19 Pandemic: The Social Costs and Legal Implications of a Health Crisis - Peršak, Nina (Medicine, Law & Society, 2023)
In crisis times, such as the recent health crisis brought out by the COVID-19 pandemic, society responds in a myriad of pro-social as well as negative, anti-social ways. The article starts by mentioning some broader social and regulatory responses to the pandemic that provided a backdrop to the studied phenomenon. It then looks explicitly at hate speech, unpacks the three-layered dimensions of its harmful consequences, helping to grasp the magnitude of harm caused by such pandemic-fuelled prejudice-based expression, and inspects the impact of the pandemic on such expression that is largely criminalised in Europe. The article concludes with some thoughts on the implications and lessons for the future.